PELATIHAN BAHASA INGGRIS MELALUI LAGU BAHASA INGGRIS DI UPT SD INPRES 6/80 LATELLANG - Damayanti, Armin; Harmilawati, Harmilawati; Irmayani, Irmayani (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
English learning is no longer taught as a local content program at UPT SD Inpres 6/80 Latellang because the curriculum that originally applied KTSP was changed to the 2013 curriculum. English subjects were not removed from the 2013 curriculum but are also not required in every elementary school. This caused the children at UPT SD Inpres 6/80 Latellang to be unfamiliar with English. The method of implementing this English training uses a service learning method assisted by ATK media and speakers. The results show that most students feel interested in teaching English through songs. This is evidenced by the increased memory related to the material being taught and the student’s interest in learning English.